Rancang Bangun Sistem Monitoring Suhu dan Kelembaban Tanah pada Media Tanam Berbasis Mikrokontroler ATMEGA328P - Putri Islam Nur Hikmah; Mislan Mislan; Rahmiati Munir (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2021)
Information of temperature and humidity in planting media is very important for cultivation activities and the process of plant growth, where the real time process is very useful to determine the watering process on planting media. The purpose of the research that has been done was to design a monitoring system for soil temperature and humidity on the planting media and to make an automatic plant watering sprinkler by detecting soil moisture. A design for monitoring soil temperature and humidity on planting media has been made with a microcontroller. This instrument works when the pump detects soil with a range ​​from 0-3 cm/Hg for dry, 3.1-6 cm/Hg for moist and 6-7.9 cm/Hg for wet. When the soil is dry, the pump will work by removing water and stop when the soil is damp or wet.